2020
DOI: 10.1186/s13019-020-1077-6
|View full text |Cite
|
Sign up to set email alerts
|

Do storage solutions protect endothelial function of arterialized vein graft in an experimental rat model?

Abstract: Background: This study aims to compare the effects of storage solutions commonly used in coronary artery bypass grafting on the vascular reactivity in vein graft interposed in arterial position in syngeneic rats. Methods: Twenty-seven male Lewis rats were sacrified to sample a vein graft implanted 6 weeks ago into abdominal aorta position. The vein grafts were inferior venae cavae initially pretreated with heparinized saline solution (HS) or autologous heparinized blood (AHB) or our referent solution, GALA. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…More recently, in an ex vivo analysis of SVG, Wise et al similarly reported that preservation in GALA enhanced tissue contractile responses and maintained vasorelaxation responses relative to unprepared grafts as measured in a muscle bath using a force transducer [25]. Meanwhile, in a syngeneic rat model, Fouquet et al reported that grafts preserved in GALA had higher rates of graft thrombosis compared to AHB (83.3% vs. 22%; P ¼ 0.04) and did not reduce the risk of intimal hyperplasia compared to control as measured by vessel wall thickness [22]. However, as highlighted by Caliskan et al, the reference GALA solution used by Fouquet and colleagues was notably different in composition to both the original GALA solution and the commercially available DuraGraft, thereby challenging their conclusions about its lack of efficacy [26].…”
Section: Buffered Solutionsmentioning
confidence: 96%
See 1 more Smart Citation
“…More recently, in an ex vivo analysis of SVG, Wise et al similarly reported that preservation in GALA enhanced tissue contractile responses and maintained vasorelaxation responses relative to unprepared grafts as measured in a muscle bath using a force transducer [25]. Meanwhile, in a syngeneic rat model, Fouquet et al reported that grafts preserved in GALA had higher rates of graft thrombosis compared to AHB (83.3% vs. 22%; P ¼ 0.04) and did not reduce the risk of intimal hyperplasia compared to control as measured by vessel wall thickness [22]. However, as highlighted by Caliskan et al, the reference GALA solution used by Fouquet and colleagues was notably different in composition to both the original GALA solution and the commercially available DuraGraft, thereby challenging their conclusions about its lack of efficacy [26].…”
Section: Buffered Solutionsmentioning
confidence: 96%
“…Furthermore, in a retrospective, nonrandomized, observational analysis of 1828 patients and 4343 SVG from the PREVENT IV trial, Harskamp and colleagues reported that AHB was associated with higher VGF at 1 year as compared to buffered saline in both patient-level (odds ratio, OR 0.62, 95% confidence interval, CI [0.46–0.83], P = 0.001) and graft-level comparisons (OR 0.63, 95% CI [0.48–0.81], P < 0.001)[21]. Conversely, Fouquet et al demonstrated that AHB had significantly lower rates of graft thrombosis at 6 weeks in an in vivo rat model as compared to the buffered solution L-glutathione, L-ascorbic acid, L-arginine and D-glucose (GALA) (22% vs. 83.3%; P = 0.04) [22]. Additionally, Chen et al reported that the hypoxic microenvironment in AHB was favorable for SVG preservation in their comparative biochemical analysis of 162 SVG samples from 21 patients stored in AHB or heparinized normal saline.…”
Section: Preservation Solutionsmentioning
confidence: 99%
“…We appreciate the interest and comments from Dr. Caliskan and colleagues [ 1 ] about our recently published article [ 2 ]. We fully agree that many confounding factors of our experimental study may alter potential beneficial effects of storage solutions reason that the results must be interpreted with caution.…”
mentioning
confidence: 99%
“…Preservation solutions to improve graft patency: The devil is in the detail Etem Caliskan 1,2 , Catherine J. Pachuk 3 , Louis P. Perrault 4 and Maximilian Y. Emmert 1,2* We read with great interest the article by Fourquet and colleagues exploring whether autologous heparinized blood (AHB), heparinized saline (HS) and GALA (considered as their reference solution) have a protective effect on vein grafts interposed in the arterial position at 6 weeks post grafting in a syngeneic rat model [1].…”
mentioning
confidence: 99%
“…We read with great interest the article by Fourquet and colleagues exploring whether autologous heparinized blood (AHB), heparinized saline (HS) and GALA (considered as their reference solution) have a protective effect on vein grafts interposed in the arterial position at 6 weeks post grafting in a syngeneic rat model [ 1 ].…”
mentioning
confidence: 99%